The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jne.12459
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for the secretogranin II‐derived peptide EM66 in the hypothalamic regulation of feeding behaviour

Abstract: EM66 is a conserved 66-amino acid peptide derived from secretogranin II (SgII), a member of the granin protein family. EM66 is widely distributed in secretory granules of endocrine and neuroendocrine cells, as well as in hypothalamic neurones. Although EM66 is abundant in the hypothalamus, its physiological function remains to be determined. The present study aimed to investigate a possible involvement of EM66 in the hypothalamic regulation of feeding behaviour. We show that i.c.v. administration of EM66 induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…EM66 has been identified in adult and fetal human adrenal gland (1) and subsequently in rat and bovine adrenochromaffin cells (2, 3). In rodents, EM66 immunoreactivity was also found in several hypothalamic regions (4, 5), which suggests several neuroendocrine roles for EM66 as it was proposed recently for the control of feeding behavior (6, 7). Moreover, we have previously demonstrated that measurement of tissue concentrations of EM66 may help to discriminate between benign and malignant pheochromocytomas (810) and that EM66 is secreted from pheochromocytoma tissue (11) and represents a sensitive plasma marker that should be considered as a complementary tool for the diagnosis and follow-up of pheochromocytoma (1214).…”
Section: Introductionsupporting
confidence: 61%
“…EM66 has been identified in adult and fetal human adrenal gland (1) and subsequently in rat and bovine adrenochromaffin cells (2, 3). In rodents, EM66 immunoreactivity was also found in several hypothalamic regions (4, 5), which suggests several neuroendocrine roles for EM66 as it was proposed recently for the control of feeding behavior (6, 7). Moreover, we have previously demonstrated that measurement of tissue concentrations of EM66 may help to discriminate between benign and malignant pheochromocytomas (810) and that EM66 is secreted from pheochromocytoma tissue (11) and represents a sensitive plasma marker that should be considered as a complementary tool for the diagnosis and follow-up of pheochromocytoma (1214).…”
Section: Introductionsupporting
confidence: 61%
“…The hypothalamus is one of the important parts of the central nervous system, which has many functions such as balancing feeding, body temperature, and regulating endocrine. It can activate an emergency response to stressors in the environment ( 13 ). The hypothalamus-pituitary-adrenal (HPA) axis plays an important role in stimulating and integrating various physiological and neural responses to adverse stimuli ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Corticosterone (COR) is a glucocorticoid secreted by the adrenal cortex and has important implications for the HPA axis. COR is a sensitive index of HS response and is related to the metabolic rate and the caloric production of broilers ( 13 ). The increase in COR indicates that the HPA system is activated in response to HS ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…CgB (formerly known as secretogranin I [15]) regulates the release of parathyroid hormones and is localized at chromaffin granule along with CgA [4]. CgC (formerly known as secretogranin II [15]) is also found in the nervous system [16] and is hypothesized to be a potential linker between the nervous and the immune systems [17]. Because human CgA is a crucial biomedical marker with a variety of functions in vivo, we will focus on human CgA in this review.…”
Section: Introductionmentioning
confidence: 99%